Diabetic Retinopathy: Retina‐Specific Methods for Maintenance of Diabetic Rodents and Evaluation of Vascular Histopathology and Molecular Abnormalities. Issue 3 (1st September 2015) - Veenstra, Alexander; Liu, Haitao; Lee, Chieh Allen; Du, Yunpeng; Tang, Jie; Kern, Timothy S.
Abstract : Diabetic retinopathy is a major cause of visual impairment, which continues to increase in prevalence as more and more people develop diabetes. Despite the importance of vision, the retina is one of the smallest tissues in the body, and specialized techniques have been developed to study retinopathy. This article summarizes several methods used to (i) induce diabetes in mice, (ii) maintain the diabetic animals throughout the months required for development of typical vascular histopathology, (iii) evaluate vascular histopathology of diabetic retinopathy, and (iv) quantitate abnormalities implicated in the development of the retinopathy. © 2015 by John Wiley & Sons, Inc.